Materials Management Practices on Public Projects in the Upper West Region - Aasonaa, Domini Naaemwan (Journal of Sustainable Materials Processing and Management, 2022)
In project construction, materials constitute a major cost item of the project, making material management a key component of project success and profit maximization. Using a cross sectional survey design, this study explored materials management practices on construction sites and the emerging challenges in material management in the Upper West Region of Ghana. A total of 129 respondents of project site managers, project consultants and the Districts/Municipals Engineers were involved in the study. The study established that the practices adopted by companies include; purchasing of materials, material planning methods, transportation of materials, material handling and inventory management. The challenges include; burglary and vandalism on material, poor qualification of the contractor’s technical staff assigned to the project, and lack of storage space for material on site. Given the existing materials management practices, the paper argues for the adoptions of technology-based material planning and handling methods. This requires capacity building on the adoption and use of technology in material management.